Polyethersulfone/MWCNT nanocomposite scaffold for endometrial cell culture: preparation, characterization, and in vitro investigation. (6th January 2021) - Alavije, Ali Alirezaei; Barati, Farid; Barati, Mohammad; Nazari, Hasan; Karimi, Iraj
Abstract: Endometrial cell culture is a method for investigating physiological or pathological conditions or simulating in vivo conditions for embryo culture. The natural function of the endometrium depends on a polarized epithelium and 3D stromal compartments. The polymer-based scaffolds of simple polyethersulfone (PES), laser scratched PES (PES-LS), and multiwall carbon nanotubes (MWCNT) composited PES (PES-MWCNT) were prepared and used for bovine endometrial cells (bECs) culture. For better investigation of the relationship between physical structure and cell growth behavior, the surface morphologies of the scaffolds were evaluated by atomic force microscopy (AFM) and field emission scanning electron microscopy (FESEM) techniques. Three synthesized membranes (PES, PES-LS, and PES-MWCNT) were evaluated for the cell morphology, viability and, doubling time. Results showed acceptable physical and chemical fabrication of the polymers with no significant differences in the proportions of live cells to primary cultured cells, dead to live cells, and the cell doubling time among groups during the experiment (P > 0.05). Total cell count (live and dead cells) was significantly different on Day 2 among types of polymers. The results showed the comparable potential of the PES-MWCNT membrane for the bECs culture.